Performance assessment of a low-cost, scalable 0.5 kW alkaline zero-gap electrolyser - Bill Gannon (International Journal of Hydrogen Energy, 2022)
The performance of a six-cell zero-gap electrolyser with an active area of 300 cm2 was analysed. The device featured a new design of flowplate that employed spot-welding in order to eliminate machining costs. Direct resistance measurements were made, and computer simulations performed to confirm the sub milli-ohm resistance of the flowplate design. An electrolyser test-rig was constructed to permit performance characterisation with various electrolytes and membranes at varying temperatures, and versus a comparable finite-gap design. The results were fitted to a simplified four-parameter model which permitted quantitative comparison, and performance projection up to a 100 kW device. The highest performance achieved was 84% efficiency with 6 M KOH at 65 °C and 400 mA/cm2, and the cell voltage was still below 2 V at 800 mA/cm2. The total material cost to build a 0.5 kW electrolyser is under 50 GBP (70 USD).